Neuroticism in Young Women with Fibromyalgia Links to Key Clinical Features. (19th February 2012) - Malin, Katrina; Littlejohn, Geoffrey Owen
Abstract : Objective . We examined personality traits in young women with FM, in order to seek associations with key psychological processes and clinical symptoms. Methods . Twenty-seven women with FM and 29 age-matched female healthy controls [HC] completed a series of questionnaires examining FM symptoms, personality and psychological variables. Results . Significant differences between characteristic FM symptoms (sleep, pain, fatigue, and confusion) as well as for the psychological variables of depression, anxiety, and stress were found between FM and HC (P < 0.001 ). Neuroticism was the only subscale of the Big Five Inventory that showed a significant difference between the FM group and HC group [P < 0.05 ]. Within the FM group, there was a significant association between the level of the neuroticism and each of pain, sleep, fatigue, and confusion, depression, anxiety, and stress (P < 0.05 –0.01). The association between the level of neuroticism and the level of stress was the strongest of all variables tested (P < 0.001 ). Conclusion . The personality trait of neuroticism significantly associates with the key FM characteristics of pain, sleep, fatigue and confusion as well as the common co-morbidities of depression, anxiety and stress. Personality appears to be an important modulator of FM clinical symptoms.